Model Pembelajaran RADEC: Bagaimana Pengaruhnya Terhadap Keaktifan Belajar Peserta Didik? - Ruswanto; Beti Susilawati; Pina Rama Deani (WISE Pendidikan Indonesia, 2026)
This study aimed to analyze the effectiveness of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model in improving students’ learning activeness in Islamic Religious Education at SMP Negeri 1 Purbolinggo. The study employed an experimental method using a Posttest-Only Control Group Design. The sample consisted of two eighth-grade classes selected through simple random sampling: an experimental class taught using the RADEC model and a control class taught through conventional methods. The research instrument was a learning activeness questionnaire that had been tested for validity and reliability, with a Cronbach’s Alpha value of 0.82. Data were analyzed using normality, homogeneity, and pooled variance t-tests. The findings revealed that the RADEC learning model had a significant effect on students’ learning activeness, with a significance value of 0.035 < 0.05. Improvements were observed in students’ critical thinking, discussion participation, problem-solving abilities, and creative idea development. The novelty of this study lies in the implementation of the RADEC model in Islamic Religious Education at the junior high school level, focusing on learning activeness. This study contributes to the development of active, collaborative, and meaningful learning strategies.